biomedicalresearch 2019
DOI: 10.35841/biomedicalresearch.30-19-257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fibre food mix on lipid profile and body weight in obese subjects

Abstract: The study aimed to assess the efficacy of developed high fibre food mix on the management of obesity. The high fibre food mix was developed by using region specific ingredients. The dietary intervention was carried out on obese rural farm women for a period of 120 days by providing 1/3 rd daily requirement of protein and energy. Impact of food mix was evaluated by assessing somatic and biochemical parameters at pre and post dietary intervention. The developed mix contained protein (15.80 ± 0.32g), fat (2.60 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
“…Building upon the information provided in the previous chapter, the application of different combinations of fiber has been identified as a desirable approach to enhance the physicochemical and nutritional properties of baked goods in the future (Chen et al, 2017; Geetha et al, 2019). Because of this, mixtures of fibers are already present in nature within by‐products sourced from the food industry (Neylon et al, 2021; Schettino et al, 2021; Stelick et al, 2021; Waters et al, 2013).…”
Section: Perspectives/future Strategiesmentioning
confidence: 99%